Effect of viscoelastic thermal compression (VTC) treatment on density and moisture content of laminas from Paraserianthes falcataria - Charles Michael Albert; Liew, Kang Chiang (2020)
Paraserianthes falcataria, a low-density wood species underwent viscoelastic thermal compression (VTC) treatment, which was the combination of pre-steaming and compression by hot-pressing, in order to increase its density and mechanical performance. The aim of this study was to evaluate the impact of VTC treatment on the density and moisture content of Paraserianthes falcataria laminas. Several process conditions which consisted of pre-steaming duration (0–30 minutes) and hot-pressing pressure (0–8 MPa) were applied on Paraserianthes falcataria laminas. Density and moisture content of Paraserianthes falcataria laminas were measured for 7 days. This study found out that process condition of 30 minutes pre-steamed combined with 8 MPa pressing pressure obtained the highest percentage of densification degree (83.71%) based on time period of before the treatment until the next 7 days after VTC process; and the lowest percentage of density improvement was recorded on non-pre-steamed combined with 4 MPa pressing pressure (54.23%). In terms of moisture content, process condition of non-pre-steamed combined with non-hot-pressed recorded the highest equilibrium moisture content (9.5%); while non-pre-steamed combined with 4 MPa pressing pressure had the lowest equilibrium moisture content (6.3%).